2017
DOI: 10.1002/nbm.3878
|View full text |Cite
|
Sign up to set email alerts
|

Combination of surface and ‘vertical’ loop elements improves receive performance of a human head transceiver array at 9.4 T

Abstract: Ultra-high-field (UHF, ≥7 T) human magnetic resonance imaging (MRI) provides undisputed advantages over low-field MRI (≤3 T), but its development remains challenging because of numerous technical issues, including the low efficiency of transmit (Tx) radiofrequency (RF) coils caused by the increase in tissue power deposition with frequency. Tight-fit human head transceiver (TxRx) arrays improve Tx efficiency in comparison with Tx-only arrays, which are larger in order to fit multi-channel receive (Rx)-only arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 41 publications
2
59
0
Order By: Relevance
“…These elements have out‐of plane currents, which are linearly independent of surface currents and hence add to the overall SNR. At 9.4 T, Avdievich was able to show an SNR boost of approximately 30% in the brain center when combining eight vertical loops with 8 surface loops . This increase is much higher than what could be expected when using 16 surface loops .…”
Section: Discussionmentioning
confidence: 81%
“…These elements have out‐of plane currents, which are linearly independent of surface currents and hence add to the overall SNR. At 9.4 T, Avdievich was able to show an SNR boost of approximately 30% in the brain center when combining eight vertical loops with 8 surface loops . This increase is much higher than what could be expected when using 16 surface loops .…”
Section: Discussionmentioning
confidence: 81%
“…To decrease radiation losses and coupling between non‐adjacent loops, the array is shielded with the cylindrical shield placed at a 40‐mm distance from the surface loops located in the second row. The distance to the shield was chosen based on previously published data for UHF human head size arrays . Because the original 2 × 8 TxRx‐array lacks RF elements at the superior locations of a head, both Tx and Rx performances in this area are rather poor .…”
Section: Methodsmentioning
confidence: 99%
“…The addition of such a large number of Rx‐only elements would substantially complicate the EM model, which in turn greatly increases the amount of the computational time and memory. However, previous EM modeling and experimental evaluation of the simpler 16‐element prototype of the array, which consisted of 8 surface TxRx loops and 8 vertical Rx loops, demonstrated that the addition of Rx‐only vertical elements practically did not alter the Tx performance and maximum local SAR . As a result, we did not include vertical loops in the simulations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem is more pronounced for a short dipole given that it does not have as broad a frequency band as a full‐length half‐lambda dipole antenna . An alternative method of producing dipole‐like currents on the cylindrical surface of the head array holder has been described recently . In this design, Rx‐only “vertical” loops were added to a single‐row array of 8 TxRx surface loops circumscribing a head.…”
Section: Introductionmentioning
confidence: 99%